Sedação, gravidade, mortalidade, delirium subsindromático e delirium em pacientes de terapia intensinva - Bastos, Alessandra Soler (2017)
The use of sedation in critically ill patients is necessary because it provides anxiolysis, aminosia, and comfort when mechanically ventilated. However, it may be a risk factor for the development of delirium in these patients, increasing length of hospital stay and mortality. Objective: To identify delirium and subsyndromal delirium in critically ill patients and to associate it with age, length of hospital stay, mortality, sedation administered, medical specialty of hospitalization and predictive scale of mortality Sepse Related Organ Failure Assessment. Methods: A cross-sectional study was conducted in a teaching hospital with 157 patients using the Richmond Agitation-Sedation Scale for sedation evaluation and Intensive Care Deli¬rium Screening Checklist for delirium evaluation. Results: Most patients presented subsyndromal delirium. The relationship between delirium and the subindromous with the time of intensive care hospitalization was statistically significant for both, while age was significant only in subsyndromatics. The most commonly used sedatives were fentanyl, midazolan, propofol and clonidine. There were significant differences between delirium and clonidine use, and subsindromatic delirium with fentanyl and midazolan. Most were discharged from the intensive care unit and the main medical specialty was neurosurgery. There were no significant differences between mortality, occurrence of discharge and death and medical specialty. Conclusion: The daily evaluation by nurses for identification and monitoring of subsyndromal delirium in intensive care patients assists in the adoption of measures that minimize the stressors that trigger delirium. The evaluation of the use of sedation by the nurse is necessary since the patients who used some sedative presented more delirium than those who did not use.